CuS@Cu-CD composites as efficient heterogeneous Fenton-like catalysts for the photodegradation of tetracycline. Issue 3 (13th February 2023) - Cheng, Yong; Deng, Lin; Wang, Dan; Wang, Xiuxiu; Ji, Changchun; Zhou, Ying-Hua
Abstract : CuS@Cu-CDs composites as Fenton-like photocatalysts for the degradation of tetracycline. Abstract : In this work, CuS@Cu-CD composites were synthesized and employed as Fenton-like catalysts. CuS significantly enhanced the photodegradation activity of tetracycline (TC) when decorated with Cu-doped-carbon dots (Cu-CDs). The influence of initial pH, dosage of catalyst, and H2 O2 concentration on the catalyst performance was investigated. Radical trapping experiments proved that ·O2 − and h + played critical roles and ·OH played a moderate role in the degradation of TC. Mechanism analyses demonstrated that Cu 2+ /Cu + redox circulation could be accelerated by the introduction of Cu into carbon dots, which further facilitated H2 O2 consumption and resulted in higher TC degradation efficiency.